3D distribution of envelope trace heights related to ground surface smoothness in CNC grinding of free-form surface. (25th October 2010) - Xie, J.; Zhou, R.M.; Zhong, Y.G.
The dispersed calculation of envelope trace heights was proposed in CNC grinding of free-form surface. The aim is to understand how 3D distribution of envelope trace heights affects ground surface smoothness. First, the 3D tool path surface was constructed to plan 3D tool paths, and then the dispersed envelope trace heights were calculated using the interference section between adjacent wheel profiles. Finally, a CNC grinding experiment was carried out to investigate the relation between envelope trace height distribution and ground surface smoothness. The results show that the dispersed calculation of envelope trace height can be used to display its distribution on 3D ground curve surface. It is confirmed that the envelope trace height depends on the slope of ground curve surface. The smooth curve surface can be gradually generated when the envelope trace height is less than 2 μm.